Utilizing Bibliotherapy Within Language Arts Instruction Can Increase and Contribute to Students’ Mental Health and Overall Well-Being (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Research has shown that there is a rise in mental health issues amongst young children, causing concern to educators. In order to help students, teachers have engaged in the therapeutic technique, bibliotherapy, which revealed positive effects on overall student mental health. Likewise, the combination of bibliotherapy and Language Arts has not only helped children with mental disorders, but it has also allowed other students to empathize and understand what peers are experiencing. There are several techniques educators can use to incorporate bibliotherapy into the curriculum such as the interactive read-aloud during whole-group instruction. With open communication and collaboration with colleagues, teachers have been able to successfully implement bibliotherapy into Language Arts instruction and significantly support the mental health of students.
Keywords: bibliotherapy; Language Arts; children's books; interactive read-aloud